ANALYSIS OF THE IMPACT OF INFLATION REDUCTION ON OUTPUT AND UNEMPLOYMENT IN NIGERIA - Richardson Kojo Edeme; Ugbor I Kalu; Chisom Emecheta; Ebikabowei Biedomo Aduku (Universitas Negeri Malang, 2018)
It has been enunciated that it is possible to reduce the size of the sacrifice ratio in an economy without a corresponding increase in the rate of inflation. Besides, for the Nigerian economy, there are issues relating to the inflation-output relationship, among which is how inflation inertia impacts on output and unemployment. It is therefore apt to ascertain what Nigeria’s sacrifice ratio could be after many successful inflation reductions over the years. Adopting the Instrumental Variables Generalized Method of Moments (IV-GMM) technique and using data from1970-2015, the findings suggest that inflation inertia has a significant negative impact on the actual rate of inflation in Nigeria. It was also revealed that the percentage of a year’s real GDP that must be forgone to reduce inflation by 1 percent in Nigeria is 5.1 while 53.6 percent of output was sacrificed in 1982. Equivalently, a sacrifice of 26.6 percent of cyclical unemployment was made in the same year; while the highest percentage of GDP was sacrificed in 1990 and the lowest in 2007.Keywords: Inflation inertia, sacrifice ratio, output, unemploymentJEL Classification: C22, E61, P44